Nanobody as a New Generation of Functional Proteins: Nanobody as a new functional domains - Ebrahimi, Zahra; Arezumand, Roghaye; Ramazani, Ali (Iranian Journal of Pharmaceutical Sciences, 2018)
Nanobody (Nb) or VHH is the smallest binding domain of camelid heavy chain antibody (HcAb). Light chains of HcAb naturally removed and because of some evolutionary changes, Nbs have unique properties rather than conventional antibodies. The size of Nb is about one-tenth (0.1) of whole antibodies and this size improved some problems of four chains antibodies such as high yield of expression in prokaryotic systems and penetration to tissues. Some other characteristics of Nb like close homology to human VH, high stability in the extended range of pH and temperature, and the capability to the identification of unusual epitope are very attractive for research and development of new Nb candidates for diagnosis, research, and therapeutic applications. Discovery of Nb almost coincided with advancement in phage display technology that was used along with Hybridoma technology in monoclonal antibody development. Currently, many of research groups focused on high-quality Nbs development against different targets especially in cancers and fortunately there are many of Nbs in clinical trial stages for use in extended ranges of diseases such as cancers, autoimmune, inflammatory diseases, and infectious diseases. Recently two of them were approved for clinical use. Big companies like Ablynx and Merck have been invested in this field and in future, further drugs base Nbs were approved in different areas of health science. In this review, we focused on production, features, and clinical application of Nbs and will be noted to Nbs in clinical trials.